Examination of Total Cholesterol Levels in the Elderly with Hypertension (Case Study at Abiansemal I Health Center, Badung Regency-Bali) - Komang Ayu Adinda Paramitha Triyani; Heri Setiyo Bekti; I Gusti Agung Ayu Dharmawati (Laboratory Journal of Infectious Diseases, 2025)
An elderly person is someone who is 60 years or older. As we age, changes in the structure and function of cells, tissues, and organ systems occur in the body, increasing the risk of hypertension. Hypertension is a multifactorial disease that can be caused by cholesterol. Hypercholesterolemia can clog peripheral blood vessels, thereby triggering hypertension. The purpose of this study was to describe total cholesterols levels among elderly individuals with hypertension at Abiansemal I Health Center, Badung Regency, Bali. This type of study used is descriptive research using non-probability techniques, purposive sampling. Total cholesterol levels were measured using the POCT method in 44 elderly participants with hypertension; 14 individuals had borderline cholesterol levels, and 17 individuals (38,6%) had high total cholesterol levels. Based on the characteristics of the respondent's dominant gender with High cholesterol levels in women were 10 people (22,7%). Based on Body mass index (BMI) is dominant among respondents with high total cholesterol levels in the normal BMI category there were 11 people (25,0%). It can be concluded that most elderly individuals with hypertension at Abiansemal I Community Health Center had high total cholesterol levels.